Development of Mechanism and Monitoring System for Surveillance and Emergency Risk Response to Promote Health Literacy on COVID-19 Pandemic - จันทวิบูลย์ อัมพร; คล้อยเอี่ยม สายชล; โรมา วิมล; ชำนาญคง กิ่งพิกุล (Journal of Health Science of Thailand, 2021)
The objective of this research was to develop an integrated risk response system for health literacy (RRHL) during the COVID–19 pandemic. The implementation of the system took place from January to August 2020. Nine departments under the Ministry of Public Health (MOPH) were involved and had learnt the development processes and capacity buildings for an effective RRHL in order to improve health literacy and self-protection against COVID–19 among Thais. It was a daily routine that risks from news and messages spread through the social media were monitored and screened by experts. In total, there were 1,650 news messages recorded in the system, 971 messages (58.85%) were related to COVID–19 of which 731 (75.28%) were given a high risk label. The response was performed for 166 risk messages (17.10%). The main channel for disseminating the responses was through the Department of Health’s website ‘Sa-suk Sure’ that had accumulative views of 4.56 million. All the responses were discussed and verified by experts before sending to the MOPH’s Emergency Operation Center for COVID-19 for making decisions on public communications. The final decisions were subsequently forwarded to the Center for COVID-19 Situation Administration for public announcements. Thus, the RRHL initiated by the Department of Health implemented together with other departments could be a starting point for Government 4.0 framework, and become a benchmark for further developments of more efficient and prompt COVID–19 response system.